“Frustrating, Stressful, and Overwhelming”: Insights into Software Practitioners’ Productivity from Stack Exchange Discussions - Silva, Júlio César Andrade; Cerqueira, Lidiany; Santana, Beatriz; Carneiro, Glauco de Figueiredo; Freire, Sávio; Mendonça, Manoel; Santos, José Amancio Macedo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.9914, 2025)
Context: Productivity is a central concern in software engineering, but traditional approaches often overlook the human aspects of daily work. Aims: To investigate how software practitioners perceive productivity challenges and how they impact their well-being and their tasks. Method: We conducted a thematic analysis of grey literature, drawing from discussions in two Stack Exchange communities (Software Engineering and Project Management). Results: We identified 21 factors that affect productivity, emphasizing time management, adopting new standards and technologies, difficulty measuring productivity, and context switching. These challenges reflect technical issues and human concerns such as demotivation and psychological pressure, showing that productivity cannot be understood in isolation. The study also revealed 17 direct impacts on professionals, including stress and perceived fluctuations in productivity, and 8 impacts on tasks, such as delays and rework. Conclusion: This study offers a broader understanding of productivity in software engineering by connecting technical and human factors. It highlights the value of grey literature in uncovering underexplored dimensions of practitioners’ experiences.